Study of Guideline for the Development of Role Model Instructor, Wat Pho Massage Discipline, Post COVID-19 Era - Chaiphibalsarisdi, Puangtip; Amornnimit, Uraiwan; Phokajang, Arpaporn; Potivasttawan, Pannika; Rodkam, Runglaksamee (Journal of health and health management, 2021)
The objectives of this qualitative study were to find the meaning and characteristics of the role model instructor of Wat Pho Thai Traditional Massage Discipline. The 11 purposive key informants were being selected from 54 instructors of Wat Pho Thai Traditional Medical School. The semi-interview guideline was being used for the in-depth interview over the phone. The content analysis was being performed according to the concept of van Manen. There were six research results: 1) The meaning of the role model instructor (RMI), Wat Pho Massage Discipline (WPMD), post COVID-19, had been defined as both male and female who had passed the competency of massage, and were being registered as role model instructor of Wat Pho Traditional Medical School. Explanation of stepping into an instructor had been moving from negative to positive meaning and more positive meaning were being reported including the meaning of how to balance the teaching practicum of the Thai massage. 2) The characteristics of RMI from the experiences were; 2.1) Passed the assessment and received a certificate, providing a good massage and was being admired by customers. Continuing of learning for knowledge of massage and language, as well as demonstrate in detail to include giving consultation to students and alumni. 2.2) Teach students to have educational outcomes in all six areas: Have a code of conduct, have basic knowledge, have intellectual skills, have a good relationship, have proper communication and massage skills. 2.3) Teach and exemplify a new way of living according to the philosophy of sufficiency economy. 2.4) Practice and teach to prevent the spread of COVID-19 and other diseases. 2.5) Holistic healthcare for the body, bright mind, independent, fair, without excessive profit. Provide alternative services and suitable environment. 2.6) Confident in health safety for service providers, recipients and related parties. To be free from fear, paranoia, anxiety and danger both sexual harassment and the economy.